Analisis Model Evaluasi Pemberdayaan UMKM Di Kediri - Rr. Forijati (Akutansi Bisnis & Manajemen ( ABM ), 2014)
This study aims to describe and analyze the successful implementation of the empowerment aspect of context, input, process, product. This study using CIPP model. The methodology used is a combination method (Mixed Methods) with design verification sequence (Sequential Explanatory). CIPP research instruments were tested to obtain valid and reliable instrument. The variables of this study consisted of: (1) The level of success of the SME development program component context, (2) The level of success of the SME development program component inputs, (3) The level of success of the SME development program component process, and (4) The success rate of the MSME program product components. The results of this study indicates that: (1) The level of success of the SME development program component context with a mean score of 4.07 or 81.4% is included in the category of very high, (2) The level of success of the MSME program input component with a mean of 4.00 or 80 % included in the very high category, (3) The level of success of the MSME program components demgam process mean 3.79 or 75.8% are high, (4) The success rate of the MSME program product components with a mean of 4.00 or 80% including in the very high category.